"No One Cares if You Can't Work": Injured and Disabled Mexican‐Origin Workers in Transnational Life Course Perspective. (19th November 2018) - Unterberger, Alayne
Abstract: What happens to injured immigrant workers as they age? What effects do their return migrations have on families, communities, and labor dynamics back home? This paper takes a composite of five immigrant families who participated in a long‐term binational study between Mexico and Florida, along with a separate cohort of Latino immigrant workers engaged in construction and warehousing in order to contextualize workers' health through Life Course Theory (LCT). This article specifically explores the lives of injured im/migrant workers and demonstrates the syndemic effects of Florida's lax workers' compensation (WC) system and intersecting health and labor policies and practices that exacerbate structural vulnerabilities on both sides of the U.S.–Mexico border. Syndemics combined with LCT highlights the intersecting and synergistic effects of place/environment, timing, timeline, and equity on health over the lifespan. Work‐related injuries, illnesses, and fatalities across different sectors of Florida's pro‐business economy exacerbate vulnerabilities and traumas, creating disability, and further inequalities in both the sending and receiving communities. The lack of effective workplace safety and health regulations perpetuate cycles of injury, illness, addiction, and precarity in both the United States and Mexico. These phenomena, combined with existing morbidities, fuel a binational disability syndemic that robs communities on both sides of the border of their economic, human, and social capital. Suggestions for different kinds of engagement and involvement by anthropologists and other social and health scientists are proposed, including discussions and examples of promising social movements attempting to hold Florida's food and agribusinesses accountable.